From a literature review to a conceptual framework for health sector websites’ assessment - Sarantis, Demetrios (2017)
Health sector institutions’ websites need to act as effective web resources of information and interactive communication mediums to address the versatile demands of their multiple stakeholders. Academic and practitioner interest in health sector website assessment has considerably risen in recent years. This can be seen by the number of papers published in journals. The purpose of this paper is twofold to further establish the field. First, it offers a literature re-view on hospitals’ websites assessment. Second, it offers a conceptual framework to address the website assessment issue in health sector. The proposed assessment framework focuses on four main criteria: content, technology, services, and participation being evaluated by the use of several indicators. Academics, hospital practitioners, public officials and users will find the review and the framework useful, as they outline major lines of research in the field and a method to assess health institution websites.